Persistence of Selective Herbicides in Rice -Rice System - Muthu Kannan M (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 2003)
The study entitled "Persistence of selective herbicides in rice-rice system" was the part of 'permanent herbicide trial' of All India Coordinated Research Programme on Weed Control conducted during the years 2001 and 2002 with the objective of determining the persistence of butachlor, pretilachlor and 2,4-D in the rice-rice cropping system. The effect of herbicides on soil microflora, weed growth and nutrient content were also studied. The field experiments were conducted during 2001 to 2002 at Agricultural Research Station, Mannuthy. Residue studies related to field experiments were conducted at Herbicide Residue Laboratory of All India Coordinated Research Programme on Weed Control, Thrissur Centre, located at Radio Tracer Laboratory, College of Horticulture, Vel1anikkara. Microbiological studies and physico chemical analysis of the soil samples were conducted at College of Horticulture, Vellanikkara. The technical programme consisted of six treatments namely (i) hand weeding twice (25 and 40 DAS); (ii) butachlor fb 2,4-D (with 100% NPK as inorganic fertilizer) in the first and second crop seasons of 2001 and 2002; (iii) butachlor fb 2,4-D (with 100% NPK as inorganic fertilizer) in the first crop season of 2001 and 2002, pretilachlor fb 2,4- D (with 100% NPK as inorganic fertilizer) in the second crop season of 2001 and 2002; (iv) butachlor fb 2,4-D (with 75% NPK as inorganic fertilizer and 25% through FYM) in first crop of2001 and 2002, pretilachlor fb 2,4-D (with 100% NPK as inorganic fertilizer) in second crop of 2001 and 2002; (v) butachlor fb 2,4-D (with 100% NPK as inorganic fertilizer) in the first and second crop of 2001, pretilachlor fb 2,4- D (with 100% NPK as inorganic fertilizer) in the first and second crop of2002 and (vi) butachlor fb 2,4- D in the first and second crop of 2001 (with 75% NPK as inorganic fertilizer and 25% through FYM in the first crop and 100% NPK as inorganic fertilizer in the second crop), pretilachlor fb 2,4-D in the first and second crop of 2002 (with 75% NPK as inorganic fertilizer and 25% through FYM in the first crop and 100% NPK as inorganic fertilizer in the second crop).